Study of Ceroluplasmin and some immunological parameters in renal failure and iron deficiency anemia patients - Ansam Hussein Ali; Sahib J. Abdurahman; Mousa J. Mohammed (Tikrit Journal of Pure Science)
The current study included 130 people over a period of research from October 2015 to May 2016 who have renal failure, iron deficiency anemia. Samples were studied divided in three groups: the first group: included 50 patients (62-20 years) with renal failure, and the second group: included 50 patients (34-5 years) from anemic iron deficiency, in addition to the 30 healthy persons (18-54 years) represented a group of healthy control. The present study aimed to find out the dynamic effect of the ceroluplasmin and its role in anemia among patients with iron deficiency anemia as well as anemia in patients with renal failure, in addition to the effect of some of the immune status in patients indicators which (IL-4), (IL-6) and (IL-10), The study concludes the following results: The results showed the presence of high-altitude CP in patients groups and for both males and females when compared with the control group. significant rise in the level of and  IL- 4, IL-6 and IL- 10 for patients with renal failure, iron deficiency anemia and thalassemia, and for both males and females